Pengaruh Kompensasi, Karakteristik Pekerjaan, dan Kepuasan Kerja Terhadap Retensi Pegawai Pada Badan Pendapatan Daerah Kota Batam - Anuar Bin Hasan; Hendri Herman; Mulyadi Mulyadi (eScience Humanity Journal, 2025)
This study aims to examine the effect of compensation, job characteristics, and job satisfaction on employee retention at the Batam City Regional Revenue Agency (Bapenda). Employee retention is a strategic issue in public sector organizations, as high turnover rates can disrupt organizational effectiveness and hinder the achievement of regional revenue targets. This research employs a quantitative approach using a survey method. The population of the study consists of all civil servants working at Bapenda Batam City, totaling 67 employees, all of whom were included as respondents using a saturated sampling technique. Data were collected through questionnaires measured using a Likert scale. The data analysis was conducted using SPSS software, applying validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that compensation has a significant effect on employee retention with a significance value of 0.003 (<0.05). Job characteristics also have a significant effect on employee retention with a significance value of 0.002 (<0.05). Furthermore, job satisfaction shows a significant effect on employee retention with a significance value of 0.001 (<0.05). Simultaneously, compensation, job characteristics, and job satisfaction significantly influence employee retention, as indicated by a significance value of 0.004 (<0.05). The Adjusted R Square value of 0.947 indicates that compensation, job characteristics, and job satisfaction collectively explain 94.7% of the variation in employee retention, while the remaining 5.3% is influenced by other factors not examined in this study. The findings of this research are expected to provide practical contributions for local government institutions in formulating human resource policies, particularly in enhancing employee retention through fair compensation systems, well-designed job characteristics, and improved job satisfaction.